Matter transfer and land use by cattle in a dehesa ecosystem of Central Spain (Vegetatio, 1992)
The transfer of matter by cattle in a 'dehesa' patureland in Central Spain has been quantified by map- ping the distribution of dung and different types of cattle behaviour in several areas distinguished by their geomorphological position, vegetation structure and management regime. Cattle show a clear preference for feeding and dung depositing in the low parts of the estate. This leads to an increase in the productivity and a rapid recycling of nutrients in the pasture communities of these areas. Comparing the relative importance of both processes in each vegetational unit, dung accumula- tion is greater in the higher zones, while in the lower areas biomass consumption is more important. This means that movement of matter by cattle tends to favour the higher ground, in a contrary direction to the downward leaching of nutrients and related processes. In the studied dehesa, this phenomena rep- resents an 'exploitation' factor of the lowland areas, which maintains productive pasture communities more immature in successional terms, by the higher woodland areas, less grazed and with low turnover. This result supports claims made in other studies that animal activity - assessed in our case by the relative impacts of herbivory and dung depositions - connect adjacent ecosystems and thus tends to improve the net energy balance of the more successionally mature part of the system. Livestock movements differ in their spatial pattern during different periods of the year: dispersing in spring and becoming more concentrated and predictable during winter. The clear seasonal differences of herbaceous production in Mediterranean climates and the management activities (basically plough- ing, tree pruning and fodder supply) are the main causes of this pattern.